Clinical efficacy and safety of TACE combined with lenvatinib and PD-1 antibody in treatment of intermediate-advanced hepatocellular carcinoma - JIANG Jiayun; ZHANG Hui; ZHANG Shiyu (陆军军医大学学报)
Objective To analyze the clinical efficacy and safety of transcatheter arterial chemoembolization (TACE) combined with lenvatinib and PD-1 antibody in the treatment of intermediate-advanced hepatocellular carcinoma (HCC). Methods A retrospective cohort trial was conducted on 105 patients with intermediate-advanced HCC (BCLC B or C stage) treated with TACE combined with lenvatinib and PD-1 antibody in our institute from January 2021 to June 2023. The blood biochemical indicators and imaging characteristics of the patients were collected before and after TACE. Objective response rate (ORR), disease control rate (DCR), conversion resection rate, overall survival (OS) and progression-free survival (PFS) were analyzed to evaluate the clinical efficacy of the triple therapy, and the frequency and severity of all adverse reactions during treatment were recorded to evaluate the safety of the therapy. Results Among the 105 patients with intermediate-advanced HCC who received triple therapy, 33 died and 72 survived. The ORR was 62.8% and the DCR was 72.3%. The conversion resection rate was 11.4%. The median OS (mOS) was not reached. The median PFS (mPFS) was (10.3±0.8) months. The incidence of adverse reactions of all grades was 97.1%, and the incidence of those of grade 3~4 was 33.3%. No treatment-related death occurred. Conclusion The triple therapy of TACE combined with lenvatinib and PD-1 antibody is a safe and effective comprehensive treatment regimen, which provides a new treatment strategy for improving the prognosis of intermediate-advanced HCC.